Neutrophil-and-monocyte-to-lymphocyte ratio is positively associated with elevated prostate-specific antigen levels and high-risk prostate cancer: evidence from the NHANES (2003–2008) - Gao, Shang; Jiang, Ping; Tian, Renli (Frontiers in Cell and Developmental Biology, 2025)
IntroductionProstate cancer (PCa) is a prevalent malignancy in men globally. The total prostate-specific antigen (TPSA) test is essential for PCa screening. The neutrophil-and-monocyte-to-lymphocyte ratio (NMLR) has emerged as a potential biomarker for various diseases, but its relationship with PCa and TPSA is yet to be studied. This research aims to explore the connection between NMLR and TPSA levels, as well as high-risk prostate cancer (HRPCa), utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2003 to 2008.MethodsThe study included 4,248 U.S. adult males. NMLR was calculated as the ratio of the combined counts of peripheral neutrophils and monocytes to the counts of peripheral lymphocytes. Weighted multiple linear and logistic regression models were used to analyze the relationship between NMLR, TPSA levels, and HRPCa.ResultsA significant positive association was found between elevated NMLR levels and increased TPSA (β = 0.35, 95% CI: 0.21–0.49), as well as higher odds of HRPCa (OR = 2.04, 95% CI: 1.55–2.68). Smooth curve fitting results indicate that there is a nonlinear positive correlation between NMLR and TPSA, as well as between NMLR and HRCa.ConclusionThis study reveals a significant relationship between NMLR, TPSA levels, and HRPCa odds among U.S. males, suggesting that NMLR could be a valuable biomarker for assessing PCa risk, underscoring inflammation’s role in prostate health. Further research is encouraged to explore its applications in early detection, treatment efficacy evaluation and risk stratification.